A comparative analysis of the post-colonial culture and democratization processes in Kenya and Zimbabwe to 2012 - Tarugarira, Gilbert (Academic Journals, 2015)
During the past four decades, no international political phenomenon has been more significant than the worldwide call and expansion of democratic governance. holding elections in almost all of Africa has turned out to be a norm. Clearly observable has been a gradual evolution of evolution of democratic institution and consolidation of democratic practices. the prospects for fostering democracy in Kenya and Zimbabwe have taken domestic and foreign- induced efforts. The basis of comparison between the two countries appears evident and tempting in a number of ways. Diagnoses of the causes of Kenya and Zimbabwe's ailments might vary spectacularly but human rights activists have accused the governments of bullying opponents in the name of preventing enemies of the state from destabilizing the nation. The presidency continued to acquire too much power. The fear that an iron grip was slowly being applied to the nations led to a steady stream of criticism of the governments with intellectuals, professionals and churches being vocal in condemning what they felt was an erosion of human rights.